INFLUENCE OF CONSTITUENCY DEVELOPMENT FUND BURSARIES ON LEARNERS’ CLASS ATTENDANCE IN PUBLIC BOARDING SECONDARY SCHOOLS IN KENYENYA SUB-COUNTY, KENYA - , Beth Syanda; George Ogochi (IJRDO- Journal of Educational Research, 2020)
Education is a profitable private investment yet many students cannot afford to finance it out of their own family resources. Awarding of bursaries to the poor and vulnerable enables such groups to access and complete school. The purpose of this study was to establish the influence of Constituency Development Fund (CDF) bursaries on Learners’ class attendance in public boarding secondary schools in Kenyenya Sub-County, Kenya. This study was inclined to the Human Capital Theory. Descriptive research design was adopted for the study. Krejcie and Morgan table was used to select a sample of 380 respondents from a target population of 25,279 individuals. Purposive and random sampling techniques were used to select the respondents. The researcher utilized questionnaires for teachers and students while an interview schedule. From the data obtained in Kenyenya sub-county, it was important for the CDF to ensure that public boarding secondary schools had an allocation of these funds even before the students enrolled in school to ensure sustenance. On assessing the extent to which provision of learning resources by CDF influence learners’ class attendance in public boarding secondary schools, it was important for schools to ensure that distribution of learning resources was be based on students’ population and not performance.